MIMO human handwriting model in stochastic environment. (20th June 2019) - Chihi, Ines; Abdelkrim, Afef
The present paper deals with a multi inputs multi outputs (MIMO) human handwriting model to characterise the pen-tip displacement on the plan from two forearm muscles activities, called electromyography signals (EMG). The proposed model takes into account perturbations and incertitude whish can affect the handwriting process (instability of the writing support, psychical state of the writer, brusque movement, etc.). In this sense, an experimental approach was presented to record the displacements of a pen-tip moving on the plane and two EMG signals during the handwriting motion. The velocity of the writing and ARMAX structure are used to characterise this biological act. Recursive extended least square (RELS) algorithm is used to estimate the parameters of the proposed handwriting model. The obtained structure shows good concordance with the experimental recorded data.